2020
DOI: 10.1007/s13365-020-00853-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in functional connectivity in people with HIV switching antiretroviral therapy

Abstract: We assessed changes in functional connectivity by fMRI (functional magnetic resonance imaging) and cognitive measures in otherwise neurologically asymptomatic people with HIV (PWH) switching combination antiretroviral therapy (cART). In a prospective study (baseline and follow-up after at least 4 months), virologically suppressed PWH switched non-nuclease reverse-transcriptase inhibitors (NNRTI; tenofovir-DF/emtricitabine with efavirenz to rilpivirine) and integrase-strand-transfer inhibitors (INSTI; tenofovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The positive relationship between variability and CD4+/CD8+ ratio may also indicate the ability of temporal variability to predict the progress of HIV in the brain or the decline of CNs immune systems. Given that the CD4+/CD8+ ratio is a more accurate hallmark of the status of the body immune system ( 93 , 94 ), we speculate that monitoring of trends of the CN CD4+/CD8+ ratio balance on differential antiretroviral therapies can be achieved through tracking the temporal variability, supporting earlier studies detecting functional changes with switching antiretroviral drugs ( 17 ). Again, since cART repairs innate CNs by reducing inflammation and enhances synoptodentritic plasticity that improves dynamic synaptic communication and neural functions ( 4 , 95 ), we hypothesize that the observed variability increases in HIV patients on stable cART might also be attributed to cART stabilization; however, further evidence is required to confirm this supposition.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The positive relationship between variability and CD4+/CD8+ ratio may also indicate the ability of temporal variability to predict the progress of HIV in the brain or the decline of CNs immune systems. Given that the CD4+/CD8+ ratio is a more accurate hallmark of the status of the body immune system ( 93 , 94 ), we speculate that monitoring of trends of the CN CD4+/CD8+ ratio balance on differential antiretroviral therapies can be achieved through tracking the temporal variability, supporting earlier studies detecting functional changes with switching antiretroviral drugs ( 17 ). Again, since cART repairs innate CNs by reducing inflammation and enhances synoptodentritic plasticity that improves dynamic synaptic communication and neural functions ( 4 , 95 ), we hypothesize that the observed variability increases in HIV patients on stable cART might also be attributed to cART stabilization; however, further evidence is required to confirm this supposition.…”
Section: Discussionsupporting
confidence: 78%
“…Alterations of striato-cortical regional activities (ReHo) and amplitude of low-frequency fluctuations (ALFF) relating to patients' CD4+T-cell counts and waning cognitive learning and memory have also been reported ( 15 , 16 ). Studies of asymptomatic HIV patients, however, have reported that antiretroviral drugs could delay or improve brain activity ( 17 ). For example, switching from efavirenz to rilpivirine appeared to improve functional connectivity of the dorsal attention network along with enhancing working memory, speed of visual processing, and executive function while switching from raltegravir to dolutegravir appeared to improve the dorsal attention and associative visual and sensory-motor networks ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A smaller clinical study of patients with controlled infection reported changes in salience and executive networks that correlated with neuropsychological test scores [ 26 ]. Other evidence suggests that during acute HIV infection, changes in resting-state functional connectivity in several brain regions correlate with depressive symptoms [ 27 ], and switching ART regimens may affect functional connectivity in asymptomatic patients [ 28 ]. Thus, functional connectivity appears to be altered in HAND patients with controlled infection and may correlate with cognitive impairment as well as other auxiliary symptoms of HAND.…”
Section: Neuroimaging and Neuropathological Studies In Hand Patientsmentioning
confidence: 99%
“… 20 To our knowledge, there are no previous studies linking fMRI networks and sleep quality in the HIV-infected population. However, it has been noted that changes in functional connectivity are seen when switching cART medications, 21 especially in the attention networks. Furthermore, patients with HIV-associated cognitive impairment show remodeling of the DMN.…”
Section: Introductionmentioning
confidence: 99%